Developing generic clinical trial animated explainer videos in the UK: results of a survey and case study - Clare Calvert; Vicki S. Barber; Duncan Appelbe; Kirsty Sprange; Claire Nollett; Fiona Lugg-Widger; Samantha Tanner; Duncan B. Richards (Trials)
Abstract Background Animated short videos used to explain a concept or project are often called animated explainer videos (AEVs). AEVs can supplement or provide an alternative to participant information sheets as a means of giving information about clinical research to potential participants. Current use of AEVs tends to focus on the specifics of a particular trial, yet there are many common aspects of clinical research regardless of the interventions being investigated that can be poorly covered in current trial materials. The EXPLAIN initiative aimed to determine the top generic clinical trial topics considered most important by different UK trial stakeholders. The top three topics were then turned into AEVs and have been made freely available for use. Method A list of generic clinical trial topics which often need explaining to potential trial participants when they are approached to take part in research was developed. Using a two-round Delphi survey of stakeholder groups (trial participants, patients, members of the public, site staff and clinical trials unit staff), the list of topics was expanded and prioritised to identify the topics most in need of clear explanation. The top three topics formed the basis of three AEVs, co-developed with patient and public partners. Results Two hundred twenty-eight responses were received to the first round of the Delphi survey, and 167 of these respondents also completed the second round of the survey. The three topics prioritised for creation of animated explainer videos were as follows: (1) What is consent? (2) Who decides what treatment I get/What is randomisation? (3) Is it safe to take part in a trial/How do you know a trial is safe? Following virtual meetings with patient and public partners recruited from the Delphi respondents, a script for each AEV was co-produced before being developed into an AEV by a company specialising in animated video production. Conclusion There are a wide range of generic concepts in which the use of animated explainer videos could be useful to improve participant understanding of clinical research. Via consensus survey across multiple stakeholders, we have determined a hierarchy of the importance of explaining these concepts. We envisage that the three AEVs created from this project will form the basis of a readily accessible library of animations to be utilised by trialists.